Peningkatan moderasi beragama masyarakat plural dalam bingkai kebhinnekaan di Desa Telagah Kecamatan Sei Bingai Kabupaten Langkat - Aulia, Adinda Putri; Lubis, Chairunnisa; Sitepu, Mhd Fadliq Ananta; Pasaribu, Zakiyah Khairani; Lubis, Fauzi Arif (Academy of Education Journal, 2024)
Religious moderation as a middle-ground approach to practicing one's faith, plays a crucial role in fostering harmony among religious communities. This article explores the significance of religious moderation in the context of Indonesia, particularly in addressing challenges such as terrorism, extremism, and intolerance. The concept of religious moderation is closely related to Bhineka Tunggal Ika, the principle of diversity that serves as the foundation of the Indonesian nation. Qualitative descriptive research methodology is employed to understand the community's perspectives on religious moderation. Data collection techniques involve interviews, observations, and case studies. Data is analyzed using qualitative analysis techniques such as thematic analysis, narrative analysis, and grounded theory. The research findings indicate that the residents of Telagah Village generally hold a positive view of religious moderation. The implementation of religious moderation in daily life, particularly through village leadership and educational approaches, contributes positively to the promotion of harmony and tolerance among religious communities. Real Work Lecture (Kuliah Kerja Nyata or KKN) emerges as an effective method for implementing the values of religious moderation at the local level and has the potential to serve as a model for other regions.